Challenges of De Jure Voter Register Accuracy and Timeliness in High Mobility Areas - Ni Putu Rulyana Kusuma Wardani; Sri Sulandari (Dynamics of Politics and Democracy, 2026)
Purpose: This study aims to analyze the implementation of the de jure-based voter data updating system and examine its challenges in ensuring accuracy and data currency, particularly in areas with high population mobility such as Tuban Village, Badung Regency. Research Methodology: The research employs a qualitative method with a descriptive-analytical approach. Data were collected through interviews, observations, and document analysis to explore the effectiveness of the voter data updating process and its alignment with actual population conditions. Results: The findings indicate that the de jure approach, which relies on administrative population data, provides legal certainty but fails to fully capture dynamic social realities. High population mobility creates discrepancies between administrative domicile and actual residence, leading to inaccuracies and outdated voter lists. Conclusions: The study concludes that voter data updating requires stronger integration between administrative legality and factual field verification to ensure that voter lists accurately reflect real population conditions. Limitations: This study is limited to a specific geographic area and relies on qualitative data, which may restrict the generalizability of the findings to other regions with different demographic characteristics. Contributions: This research contributes to the discourse on electoral governance by highlighting the need for a hybrid approach that combines administrative data systems with field-based verification, thereby improving the accuracy and reliability of voter data management.